A-3: MUHAMMAD ABDUL RASHEED NOMANI AND HIS EDUCATIONAL EFFORTS: محمد عبد الرشيد النعماني وجهوده العلمية - Ahmed, Sardar; Hayat Ullah, Syed; Ahmed, Khalil (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
Hazrat Maulana Allama Abdul Rasheed Nomani was endowed with so many excellent qualities, and it can be said that Allah Almighty made him a perfect example of his power and an all-around personality. He was an absolutely learned scholar who not only played a significant role in the promotion and development of the religion of truth but also on many occasions criticized Bidaats in a convincing manner. Maulana Nomani was undoubtedly a treasure trove of Islamic knowledge, which was used by innumerable scholars, students, and the public. Not only did he write on issues such as the difficulties of the Qur’an and the understanding and interpretation of the words of the Qur’an, but he also played an important role in bringing to light the Hadith and especially the services of Imam Abu Hanifa (may Allah have mercy on him). It proves that he has a good command of the Quran-o-Hadith, as well as is a brilliant writer in the Arabic language. All of his writings are the result of in-depth research and advanced research. He had found a scientific and researchful nature and mind. Nature had endowed him with these qualities. That is why he went beyond prejudice and wrote on such topics, which are generally misunderstood by the people. He removed many misunderstandings and distractions from the people by transcribing many very useful scholarly works in Urdu and Arabic language. In this way, Maulana Nomani was counted among the great personalities as he had served in various Madrassas and universities till the last days of his life. He was also highly regarded by contemporary scholars due to his high moral character and scholarly ability. Numerous scholars were not only acquainted with his scholarly status and high literary and research qualities but were also convinced of his good qualities. From time to time on different occasions, he seems to be openly expressing them. By the grace of God, he was at the highest level of knowledge and was a treasure trove of many genres of religious knowledge. Bringing all these things to light in an investigative manner is a fulfillment of a debt as well as a duty. For these reasons, I have chosen the personality of Hazrat Maulana Abdul Rasheed Nomani and His Religious Services as the topic for my research article.